Improving preparation and luminescence properties of Eu and dy doped Sr2MgSi2O7 phosphors by adding excess silica - Chi Zhang; Liuming Wei; Qin Liu; Ruirui Cui; Chaoyong Deng; Jingyu Li (Scientific Reports)
Abstract Solid state reaction method is most commonly used to synthesize Sr2MgSi2O7: Eu2+, Dy3+ phosphors. In order to avoid the energy waste caused by high sintering temperature, we systematically studied and optimized the preparation process of Sr2MgSi2O7: Eu2+, Dy3+ long afterglow phosphors by increasing the Si/Sr ratio in the raw materials. The appropriate addition of silica not only facilitates the preparation of single phase Sr2MgSi2O7: Eu2+, Dy3+ phosphor but also enhances the rate of solid state reaction, so as to achieve the purpose of reducing the sintering temperature. The photoluminescence performance of the sample with a Si/Sr ratio of 1.1 sintered at 1350 °C is the highest, followed by that of the sample sintered at 1400 °C with a Si/Sr ratio of 1.0. Notably, the photoluminescence properties of the Si/Sr ratio of 1.3 sample sintered at 1300 °C are comparable to those of the Si/Sr ratio of 1.0 sample sintered at 1400 °C. However, in terms of afterglow properties, the former exhibits an enhancement by a factor of 3.5 compared to the latter. This finding suggests that strategically increasing the Si/Sr ratio can reduce the sintering temperature by 100 °C while maintaining or even enhancing the luminescence and afterglow properties of the samples. Additionally, the electronic structures of the Sr2MgSi2O7 host, the doped luminescence center Eu, the oxygen vacancies and the co-doped activator Dy have been methodically investigated through first-principles calculations. By integrating the findings on the distribution of the dopants and defects levels, we predict and propose the photoluminescence and afterglow mechanisms of Sr2MgSi2O7: Eu2+, Dy3+. These studies suggest an efficient, cheap and energy-saving strategy for the preparation of Sr2MgSi2O7: Eu2+, Dy3+ long afterglow phosphor, and reveal the roles of oxygen vacancies and co-doped Dy in the afterglow luminescence.